Apology of terrorism and other related crimes: Evolution and trends in Spain and in Perú - Pastrana Sánchez, María Alejandra (2019)
The instigation of terrorism and other similar crimes that punish incitement or enhancement of terrorism are experiencing an exponential growth in its regulation all over the world. In Spain and Peru this trend is not new: since the 1990’s a large number of legal modifications have criminalized such practices. A compared and evolutive study of these crimes and the jurisprudence trends are offered in this paper.